Diagnostic and prognostic value of (18)F-DOPA PET and (1)H-MR spectroscopy in pediatric supratentorial infiltrative gliomas: a comparative study - Morana, Giovanni (Neuro Oncol, 2015)
BACKGROUND: (1)H-MR spectroscopy (MRS) and (18)F-dihydroxyphenylalanine (DOPA) PET are noninvasive imaging techniques able to assess metabolic features of brain tumors. The aim of this study was to compare diagnostic and prognostic information gathered by (18)F-DOPA PET and (1)H-MRS in children with supratentorial infiltrative gliomas or nonneoplastic brain lesions suspected to be gliomas. METHODS: We retrospectively analyzed 27 pediatric patients with supratentorial infiltrative brain lesions on conventional MRI (21 gliomas and 6 nonneoplastic lesions) who underwent (18)F-DOPA PET and (1)H-MRS within 2 weeks of each other. (1)H-MRS data (choline/N-acetylaspartate, choline-to-creatine ratios, and presence of lactate) and (18)F-DOPA uptake parameters (lesion-to-normal tissue and lesion-to-striatum ratios) were compared and correlated with histology, WHO tumor grade, and patient outcome. RESULTS: (1)H-MRS and (18)F-DOPA PET data were positively correlated. Sensitivity, specificity, and accuracy in distinguishing gliomas from nonneoplastic lesions were 95%, 83%, and 93% for (1)H-MRS and 76%, 83%, and 78% for (18)F-DOPA PET, respectively. No statistically significant differences were found between the 2 techniques (P > .05). Significant differences regarding (18)F-DOPA uptake and (1)H-MRS ratios were found between low-grade and high-grade gliomas (P≤.001 and P≤.04, respectively). On multivariate analysis, (18)F-DOPA uptake independently correlated with progression-free survival (P≤.05) and overall survival (P = .04), whereas (1)H-MRS did not show significant association with outcome. CONCLUSIONS: (1)H-MRS and (18)F-DOPA PET provide useful complementary information for evaluating the metabolism of pediatric brain lesions. (1)H-MRS represents the method of first choice for differentiating brain gliomas from nonneoplastic lesions.(18)F-DOPA uptake better discriminates low-grade from high-grade gliomas and is an independent predictor of outcome.